2015
DOI: 10.1097/bot.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Malleolar Fracture Patterns

Abstract: Mapping of posterior malleolar fractures revealed a continuous spectrum of Haraguchi III to I fractures and identified Haraguchi type II as a separate pattern. Quantification of 3-dimensional CT-modeling is reliable to assess fracture characteristics of posterior malleolar fracture fragments. Morphology might be more important than posterior malleolar fracture size alone for clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 40 publications
(75 reference statements)
4
53
0
2
Order By: Relevance
“…Some authors reported negative relationships between the fixation of small posterior malleolar fragment and the functional outcome, while others believed that the fixation of small posterior malleolar fragment would contribute to the stability of syndesmosis [2, 4, 21, 22]. Recent anatomical and clinical studies provide evidence that the morphology of the fracture fragment might be more important than the fragment size [1, 23]. A thorough study of the morphology of the fracture fragment in reconstructed CT images might provide information about the injury mechanisms, and hence guided different way of reduction and fixation [9, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported negative relationships between the fixation of small posterior malleolar fragment and the functional outcome, while others believed that the fixation of small posterior malleolar fragment would contribute to the stability of syndesmosis [2, 4, 21, 22]. Recent anatomical and clinical studies provide evidence that the morphology of the fracture fragment might be more important than the fragment size [1, 23]. A thorough study of the morphology of the fracture fragment in reconstructed CT images might provide information about the injury mechanisms, and hence guided different way of reduction and fixation [9, 24].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Subject CTs identified as malreductions were uploaded to OsiriX Dicom (Geneva, Switzerland) software and 3-dimensional reformats were created. [5][6][7] Subject CTs identified as malreductions were uploaded to OsiriX Dicom (Geneva, Switzerland) software and 3-dimensional reformats were created.…”
Section: Mapping Of Malreductionsmentioning
confidence: 99%
“…Some studies suggested that morphology of the posterior malleolar fragment might be more important than size for clinical decision making [21,31]. Haraguchi type II fracture was also considered to be posterior pilon fracture, which has more complex mechanism and more special morphological characteristics [32].…”
Section: Discussionmentioning
confidence: 99%
“…e selection of the observation plane was also affected by the position of the ankle and the experience of observers. A study tried to use three-dimensional (3D) CT to assess the articular involvement of posterior malleolar fractures [21]. But the method adopted, which needs to integrate several sets of software, was complex and time-consuming.…”
Section: Introductionmentioning
confidence: 99%